2021
DOI: 10.1002/jbio.202100157
|View full text |Cite
|
Sign up to set email alerts
|

Redox ratio in the left ventricle of the growth restricted fetus is positively correlated with cardiac output

Abstract: Intrauterine growth restriction (IUGR) is a result of limited substrate supply to the developing fetus in utero, and can be caused by either placental, genetic or environmental factors. Babies born IUGR can have poor long-term health outcomes, including being at higher risk of developing cardiovascular disease. Limited substrate supply in the IUGR fetus not only changes the structure of the heart but may also affect metabolism and function of the developing heart. We have utilised two imaging modalities, two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…However, altered cardiac maturation and energy management may also affect fetal survival during further episodes of hypoxia. For example, a recent study evaluating cardiac metabolism in growth retarded fetal sheep using two imaging modalities, two-photon microscopy and phase-contrast magnetic resonance imaging, found evidence that the FGR heart relies heavily on glycolysis for ATP production, consistent with an impaired ability to tolerate further hypoxia (Dimasi et al, 2021). We have previously shown that fetal weight was strongly associated with impaired tolerance to severe hypoxia in preterm fetal sheep, particularly in males, and that the pattern of impaired failure of tolerance to hypoxia was sex dependent (Bennet et al, 2007).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
“…However, altered cardiac maturation and energy management may also affect fetal survival during further episodes of hypoxia. For example, a recent study evaluating cardiac metabolism in growth retarded fetal sheep using two imaging modalities, two-photon microscopy and phase-contrast magnetic resonance imaging, found evidence that the FGR heart relies heavily on glycolysis for ATP production, consistent with an impaired ability to tolerate further hypoxia (Dimasi et al, 2021). We have previously shown that fetal weight was strongly associated with impaired tolerance to severe hypoxia in preterm fetal sheep, particularly in males, and that the pattern of impaired failure of tolerance to hypoxia was sex dependent (Bennet et al, 2007).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
“…Most recently, Dimasi et al . (2021) used two‐photon imaging in the caruncletomy model of IUGR and reported reduced redox ratios in the IUGR fetal heart. They conclude that this may be due to an increased reliance on glycolysis for ATP production as a reduced redox ratio is suggestive of augmented glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Barry et al (2016) found that the myocardium in fetuses compromised by IUGR is more sensitive to insulin, suggesting that placental insufficiency can modify metabolic processes in the fetal heart. Most recently, Dimasi et al (2021) used two-photon imaging in the caruncletomy model of IUGR and reported reduced redox ratios in the IUGR fetal heart. They conclude that this may be due to an increased reliance on glycolysis for ATP production as a reduced redox ratio is suggestive of augmented glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep are often used as preclinical models in cardiac physiology as they are anatomically and haemodynamically similar to humans. Late gestation IUGR fetuses have impaired expression of genes involved in glycolysis in both skeletal muscle and liver (Brown et al 2015), and a recent study used two-photon imaging to show the hearts of IUGR fetuses may have a greater reliance on glycolysis for ATP generation (Dimasi et al 2021). Additionally, there is evidence that this may persist past birth as lambs born with a low birth weight due to early onset IUGR also have a greater reliance on glycolysis for cardiac ATP production postnatally (Wang et al 2011(Wang et al , 2013.…”
mentioning
confidence: 99%
“…2015), and a recent study used two‐photon imaging to show the hearts of IUGR fetuses may have a greater reliance on glycolysis for ATP generation (Dimasi et al . 2021). Additionally, there is evidence that this may persist past birth as lambs born with a low birth weight due to early onset IUGR also have a greater reliance on glycolysis for cardiac ATP production postnatally (Wang et al .…”
mentioning
confidence: 99%